A multinational study distinguishing Alzheimer's and healthy patients using cerebrospinal fluid tau/Aβ42 cutoff with concordance to amyloid positron emission tomography imaging. Issue 1 (6th March 2017) - Mo, Yi; Stromswold, Julie; Wilson, Kimberly; Holder, Daniel; Sur, Cyrille; Laterza, Omar; Savage, Mary J.; Struyk, Arie; Scheltens, Philip; Teunissen, Charlotte E.; Burke, James; Macaulay, S. Lance; et al.
Abstract: Introduction: Changes in cerebrospinal fluid (CSF) tau and amyloid β (Aβ)42 accompany development of Alzheimer's brain pathology. Robust tau and Aβ42 immunoassays were developed to establish a tau/Aβ42 cutoff distinguishing mild‐to‐moderate Alzheimer's disease (AD) subjects from healthy elderly control (HC) subjects. Methods: A CSF tau/Aβ42 cutoff criteria was chosen, which distinguished the groups and maximized concordance with amyloid PET. Performance was assessed using an independent validation cohort. Results: A tau/Aβ42 = 0.215 cutoff provided 94.8% sensitivity and 77.7% specificity. Concordance with PET visual reads was estimated at 86.9% in a ∼50% PET positive population. In the validation cohort, the cutoff demonstrated 78.4% sensitivity and 84.9% specificity to distinguish the AD and HC populations. Discussion: A tau/Aβ42 cutoff with acceptable sensitivity and specificity distinguished HC from mild‐to‐moderate AD subjects and maximized concordance to brain amyloidosis. The defined cutoff demonstrated that CSF analysis may be useful as a surrogate to imaging assessment of AD pathology.